Long-lasting endothelium-dependent relaxation of isolated arteries caused by an extract from the bark of Combretum leprosum - Francisco das Chagas Alves Filho (Einstein (São Paulo))
Objective To describe and to characterize the relaxing effect of an extract of the bark of Combretum leprosum on isolated arterial rings from different animals.Methods Rings (3 to 4mm) from rabbit, rat, or porcine arteries rings were suspended in an organ bath (Krebs, 37°C, 95%O2/5%CO2) to record isometric contractions. After the stabilization period (2 to 3 hours) contractions were induced by the addition of phenylephrine (0.1 to 0.3µM) or U46619 (10 to 100nM), and Combretum leprosum extract was added on the plateau of the contractions. Experiments were performed to determine the potency, duration, reversibility, and to get insights on the potential mechanism involved in extract-induced relaxations.Results In all rings tested, Combretumleprosum extract (1.5μg/mL) was able to cause relaxations, which were strictly endothelium-dependent. In rabbit or rat thoracic aorta rings, the relaxations were reversed by vitamin B12a or L-NG-nitroarginine. In porcine right coronary arteries and rabbit abdominal aorta, extract caused both L-NG-nitroarginine-sensitive and L-NG-nitroarginine-resistant relaxations. In rabbit thoracic aorta, the extract was relatively potent (EC50=0.20µg/mL) and caused relaxations; intriguingly the endothelium continued to produce relaxing factors for a long period after removing the extract. The magnitude of extract-induced relaxations was significantly reduced in the absence of extracellular Ca2+; in addition, the TRPs channels blocker ruthenium red (10µM) was able to revert extract-induced relaxations. Phytochemical analyses indicated that the extract was rich in polyphenol-like reacting substances.ConclusionsCombretum leprosum extract contains bioactive compounds capable of promoting Ca2+-dependent stimulation of endothelial cells which results in a prolonged production of relaxing factors.